Seymour Papert and Us. Constructionism as the Educational Philosophy of the 21st Century - Alexei Semenov (Вопросы образования, 2017)
Seymour Papert — a major philosopher of education, a great educator of modern age, and the father of constructionism — passed away in summer 2016. The floor and screen turtles he added to the Logo programming language provided visualization and objectification of the processes, as well as conciseness of programming. As a result, Logo developed into a unique environment that millions of children in dozens of countries use to learn algorithmic (or computational) thinking. Professor Seymour Papert visited the Soviet Union and Russia a number of times. He played a key role in the establishment of the post-Soviet school’s educational philosophy. The article describes a number of crucial ideas and events associated with the development of Papert’s education philosophy, the implementation of his educational conception in Russia, his visits to Russia, and his meetings with Russian educators, which were first of all attended by the author.